Method for recycling lithium composite copper foil composite belt
By reacting in an organic solution containing carboxyl or hydroxyl groups and a nitric acid mixture, the problem of high energy consumption and low efficiency of lithium-copper composite belt recovery is solved, and the effect of efficient recovery of metal lithium, PP film and copper is achieved.
Patent Information
- Application Number
- CN202411597698.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-11
- Publication Date
- 2025-02-11
AI Technical Summary
The existing lithium-copper composite belt recycling methods have problems of high energy consumption and low process efficiency, and have failed to effectively recover metal lithium, PP film and copper.
By reacting the lithium composite copper foil composite tape in an organic solution containing carboxyl or hydroxyl groups, the metal lithium layer is dissolved, and then reacted in a nitric acid mixture to dissolve the copper layer and the separator layer, thereby realizing metal lithium, PP film and copper recycling.
The recovery of lithium composite copper foil composite belt with low energy consumption and high efficiency has been achieved. The recovery rate of metal lithium is close to 100%, and the recovery rate of copper is more than 95%.
Smart Images

Figure CN119410898A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of lithium battery recycling, and in particular to a method for recycling lithium composite copper foil composite strips. Background Art
[0002] At present, lithium batteries have been widely used in the field of new energy vehicles. Faced with the problem of spontaneous combustion of new energy vehicles, many lithium battery manufacturers use composite copper foil as battery current collector, which is conducive to improving the safety performance, energy density and compatibility of batteries, while also reducing costs. This type of current collector combined with metal lithium is called lithium copper composite tape, which leads to a new direction for downstream lithium solid-state batteries. The recycling of metal lithium and rolled PP film in discarded lithium copper composite tape is crucial.
[0003] Ultra-thin PP / PET film is used in the lithium battery industry for the following main functions: (1) As a support film, it provides tension for low tensile strength materials to pass through the roller. (2) The ultra-thin PP / PET film material itself has a large elasticity variable, which can be used to prevent lithium metal from deforming during extrusion. These two usage properties make this type of film easy to recycle and have low requirements on the material itself.
[0004] Currently, there are mainly the following methods for recycling lithium-copper composite tapes: (1) exposing the composite tape to the air to convert metallic lithium into white lithium carbonate powder. The remaining copper foil is collected and mechanically crushed, and then the residual lithium compound is washed with water and dried to achieve the purpose of recycling. This method has the disadvantages of large lithium carbonate dust and endangering the health of workers. (2) heating the heat transfer oil to between the melting points of lithium and copper, and the metallic lithium melts in the oil when passing through the heat transfer oil. The copper foil continues to be wound through the guide roller to achieve the recovery of metallic lithium and copper foil respectively. This method has problems such as high energy consumption. (3) Calcination method, the lithium-copper composite tape is put into a calcination furnace, and the residue is recovered after calcination. This method has great energy loss.
[0005] Therefore, the existing methods for recycling lithium-copper composite strips generally have the problems of high energy consumption and low process efficiency, and there is no relevant technology for the joint recovery of metallic lithium, PP film and copper.
[0006] In view of this, the present invention is proposed. Summary of the invention
[0007] The purpose of the present invention is to provide a method for recycling lithium-composite copper foil and composite strip, aiming to improve the recovery rate of metallic lithium, PP film and copper under the premise of reducing energy consumption and improving process efficiency.
[0008] The present invention is achieved in that:
[0009] In a first aspect, the present invention provides a method for recycling a lithium composite copper foil composite strip, wherein the lithium composite copper foil composite strip comprises a first metal lithium layer, a first copper layer, a diaphragm layer, a second copper layer, and a second metal lithium layer arranged in sequence, and the method comprises:
[0010] The lithium composite copper foil and composite strip are reacted in an organic solution containing carboxyl or hydroxyl groups to dissolve the first metal lithium layer and the second metal lithium layer to obtain a composite copper foil;
[0011] The composite copper foil is reacted in a nitric acid mixture to dissolve the first copper layer and the second copper layer on the surface while recovering the diaphragm layer.
[0012] In an optional embodiment, the organic solution is a mixed solution of an organic acid, an organic alcohol solvent and water, and the organic lithium salt obtained by the reaction is recovered as a pharmaceutical raw material;
[0013] Preferably, the organic acid is selected from at least one of oxalic acid, acetic acid, tartaric acid and citric acid;
[0014] Preferably, the organic alcohol solvent is ethanol, and the volume ratio of the organic alcohol solvent to water is 1:(0.5-1.5).
[0015] In an optional embodiment, the nitric oxide obtained by the reaction in the nitric acid mixture is collected, reacted with water in an oxygen-containing atmosphere to obtain a nitric acid solution, and the nitric acid solution is used to prepare the nitric acid mixture;
[0016] Preferably, the nitric acid mixture is dilute nitric acid with a mass fraction of 20%-50%.
[0017] In an optional embodiment, after the lithium composite copper foil composite strip is reacted in the organic solution, it is washed and dried, and then placed in a nitric acid mixture for reaction;
[0018] Preferably, the solvent used in the cleaning process is selected from at least one of ethanol, methanol and water; more preferably, the solvent used in the cleaning process is 50%-75% by mass ethanol;
[0019] Preferably, the drying temperature is controlled at 30°C-80°C.
[0020] In an optional embodiment, the lithium composite copper foil composite tape is processed in sequence through a lithiation zone, a first cleaning zone, a drying zone and a nitration zone through a guide roller; the lithium composite copper foil composite tape is reacted in an organic solution in the lithiation zone, cleaned with a solvent in the first cleaning zone, and then dried in the drying zone to obtain a composite copper foil; the composite copper foil reacts with a nitric acid mixture in the nitration zone and is recovered to obtain a rolled PP / PET film.
[0021] In an optional embodiment, the hydrogen generated during the reaction with the organic solution is collected and burned to provide heat for the nitrification zone;
[0022] Preferably, a first gas extraction device is provided in the lithiation zone, and organic acids, alcohols and water are filtered by a wet filter cloth in the first gas extraction device, and hydrogen is collected by a drainage method at the same time;
[0023] Preferably, the reaction is carried out in the lithiation zone using a collecting tank with a sloped bottom.
[0024] In an optional embodiment, a reel is provided at one end of the lithiation zone, a reel is provided at the end of the device, and a plurality of tension guide rollers are provided in the reaction vessels of the lithiation zone and the nitration zone, so that the lithium composite copper foil composite tape or composite copper foil is sequentially transmitted through the reel, the plurality of tension guide rollers and the reel;
[0025] Preferably, a first gas extraction device is provided at the top of the lithiation zone.
[0026] In an optional embodiment, in the lithiation zone, a first spray device for spraying downward is provided above the plurality of tension guide rollers, and a second spray device for spraying upward is provided below the tension guide rollers, and the organic solution is sprayed out by using the first spray device and the second spray device;
[0027] Preferably, the first spray device and the second spray device each include a plurality of spray heads, and the spray flow rate of each spray head is greater than 4.2×10 -3 mL / min, the diameter of the sprayed droplets is 3μm-15μm;
[0028] Preferably, the initial running speed is controlled to be 0.05 m / min-0.3 m / min, and then the unwinding speed is controlled according to the amount of collected hydrogen.
[0029] In an optional embodiment, a second exhaust device is provided at the top of the nitrification zone to collect the nitric oxide produced by the reaction through the second exhaust device; the nitric oxide collected in the nitrification zone is reacted with water under an oxygen-containing atmosphere to obtain a nitric acid solution, and the nitric acid solution is circulated to the nitrification zone;
[0030] A heating device is also provided on the nitration zone, and the heating device uses the hydrogen collected in the lithiation zone to burn and provide heat;
[0031] Preferably, after passing through the nitrification zone, the strip continues to pass through a second cleaning zone for cleaning and then is wound up.
[0032] In an optional embodiment, the thickness of the diaphragm layer is 1 μm-10 μm, the thickness of the first metal lithium layer and the second metal lithium layer are both 5 μm-100 μm, and the thickness of the first copper layer and the second copper layer are both 1 μm-3 μm;
[0033] Preferably, the separator layer is selected from at least one of a PP film and a PET film.
[0034] The invention has the following beneficial effects: reacting the lithium composite copper foil composite strip in an organic solution containing carboxyl or hydroxyl groups to dissolve the first metal lithium layer and the second metal lithium layer to obtain a composite copper foil, and the obtained organic lithium salt can be recycled as a pharmaceutical raw material; reacting the composite copper foil in a nitric acid mixed solution to dissolve the first copper layer and the second copper layer on the surface, and recovering the diaphragm layer at the same time. The process provided by the invention has low energy consumption, simple and controllable reaction, and can realize industrial recovery of metal lithium, diaphragm layer and copper metal, and the recovery rate of metal lithium and diaphragm layer is close to 100%, and the recovery rate of copper also reaches more than 95%. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0036] Figure 1 A schematic diagram of the structure of a lithium-copper-foil composite strip processed by an embodiment of the present invention;
[0037] Figure 2 A process flow chart provided for an embodiment of the present invention;
[0038] Figure 3 A distribution diagram of each area in the method provided by an embodiment of the present invention;
[0039] Figure 4 A flow chart of a device provided by an embodiment of the present invention;
[0040] Figure 5 A diagram of a device for a lithiation zone provided in an embodiment of the present invention;
[0041] Figure 6 An apparatus diagram of a nitrification zone provided in an embodiment of the present invention.
[0042] Icon: 10-lithium composite copper foil composite tape; 101-first metal lithium layer; 102-first copper layer; 103-diaphragm layer; 104-second copper layer; 105-second metal lithium layer; 106-composite copper foil;
[0043] 100-device for recovering lithium composite copper foil composite strip; 110-lithiation zone; 120-first cleaning zone; 130-first drying zone; 140-nitrification zone; 150-second cleaning zone; 160-second drying zone; 171-guide roller; 111-first open reactor; 121-first cleaning container; 131-first drying box; 141-second open reactor; 151-second cleaning container; 161-second drying box;
[0044] 001-unwinding shaft; 002-first air extraction device; 003-rewinding shaft; 004-first spray device; 005-second spray device; 006-tension guide roller; 007-second air extraction device; 008-heating device. DETAILED DESCRIPTION
[0045] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0046] like Figure 1 As shown, the lithium composite copper foil composite strip 10 processed by the embodiment of the present invention includes a first metal lithium layer 101, a first copper layer 102, a diaphragm layer 103, a second copper layer 104 and a second metal lithium layer 105 arranged in sequence, and the first copper layer 102, the diaphragm layer 103 and the second copper layer 104 form a composite copper foil 106.
[0047] In some embodiments, the first metal lithium layer 101 and the second metal lithium layer 105 may be ultra-thin metal lithium, and the thickness of the first metal lithium layer 101 and the second metal lithium layer 105 are both 5μm-100μm, and the thickness of the first metal lithium layer 101 and the second metal lithium layer 105 may be the same or different.
[0048] In some embodiments, the first copper layer 102 and the second copper layer 104 are formed of copper foil, and the thickness of the first copper layer 102 and the second copper layer 104 are both 1 μm-3 μm, and the thickness of the first copper layer 102 and the second copper layer 104 can be the same or different.
[0049] In some embodiments, the diaphragm layer 103 may be at least one of a PP film (polypropylene film) and a PET film (polyethylene terephthalate film), preferably a PP film. The thickness of the diaphragm layer 103 is 1 μm-10 μm.
[0050] The embodiment of the present invention provides a method for recycling lithium composite copper foil composite strip, comprising the following steps:
[0051] S1. Dissolved lithium
[0052] like Figure 2 As shown, the lithium composite copper foil composite tape is reacted in an organic solution containing carboxyl or hydroxyl (such as an organic weak acid solution) to dissolve the first metal lithium layer and the second metal lithium layer, so that the lithium is recovered.
[0053] In some embodiments, the organic solution is a mixed solution of an organic acid, an organic alcohol solvent and water, and the organic alcohol can be used as a cooling agent. After the lithium composite copper foil composite tape reacts in an organic solution, a related weak acid lithium salt solution can be obtained, and purified lithium salts can be obtained by heating evaporation, recrystallization, etc., and applied to the pharmaceutical raw material industry. Specifically, organic lithium reagents are important reagents that are indispensable in metal organic synthesis and are also the most important reagents in alkali metal organic compounds; in addition, organic lithium compounds can be used to treat diseases such as depression and epilepsy.
[0054] Further, the organic acid is selected from at least one of oxalic acid, acetic acid, tartaric acid and citric acid, and the organic acid can be any one or more of the above. The organic alcohol solvent can be ethanol, and the volume ratio of the organic alcohol solvent to water is 1: (0.5-1.5), such as 1: 0.5, 1: 1.0, 1: 1.5, etc. Due to the different solubilities of different organic acids, the concentrations of the corresponding organic acid solutions will also be different. The concentration of the organic acid is close to its maximum solubility in water and ethanol. For example, the solubility of oxalic acid in water is 150g / L, and the solubility in ethanol is 400g / L. The organic solution is prepared under the conditions of 5L of pure water and 5L of ethanol to make the concentration of the organic acid as large as possible, thereby increasing the concentration of the weak acid lithium salt solution.
[0055] The waste lithium composite copper foil composite tape is passed into the organic solution, and the metal lithium reacts with the organic acid solution to generate relevant organic salts. The chemical reaction equation is:
[0056] 2R-COOH+2Li=2R-COOLi+H2↑;
[0057] 2R-OH+2Li=2R-OLi+H2↑;
[0058] 2H2O+2Li=2LiOH+H2↑;
[0059] 2C2H5OH+2Li=2C2H4OLi+H2↑.
[0060] The following is the reaction principle of some organic acid solutions:
[0061] Oxalic acid solution: Oxalic acid is solid, add a small amount of water to get oxalic acid solution. The resulting product, lithium oxalate, is slightly soluble in water, with a solubility-water ratio of 8:100, and is easily separated from water.
[0062] Oxalic acid: 2C2H2O4+2Li=2C2HO4Li+H2↑;
[0063] 2H2O+2Li=2LiOH+H2↑;
[0064] 2C2H5OH+2Li=2C2H4OLi+H2↑.
[0065] Acetic acid solution: Acetic acid is liquid. Lithium acetate is obtained after the reaction, and purified lithium acetate can be obtained by recrystallization.
[0066] Acetic acid: 2CH3COOH+2Li=2CH3COOLi+H2↑;
[0067] 2H2O+2Li=2LiOH+H2↑;
[0068] 2C2H5OH+2Li=2C2H4OLi+H2↑.
[0069] Tartaric acid solution: Tartaric acid is soluble in water and is often used as a raw material in the pharmaceutical industry. Lithium tartrate usually exists as a dihydrate. In addition, the higher the temperature, the lower the solubility (42g / 0℃). Lithium tartrate crystals can be obtained by controlling the reaction temperature.
[0070] Tartaric acid: 2C4H6O6+2Li=2C4H5O6+H2↑;
[0071] 2H2O+2Li=2LiOH+H2↑;
[0072] 2C2H5OH+2Li=2C2H4OLi+H2↑.
[0073] Citric acid solution: Citric acid is a colorless crystal that is easily soluble in water. Lithium citrate usually exists in the form of tetrahydrate and loses its crystal water when heated to 105°C.
[0074] Citric acid: 2C6H8O7+2Li=2C6H7O7Li+H2↑;
[0075] 2H2O+2Li=2LiOH+H2↑;
[0076] Ethanol: 2C2H5OH+2Li=2C2H4OLi+H2↑.
[0077] like Figure 3 As shown, the step of dissolving lithium is carried out in the lithiation zone, and the hydrogen produced by the reaction with the organic acid is collected and used for heating in the nitration zone.
[0078] Figure 4 The device 100 for recycling lithium-composite copper foil composite strip is shown, including a lithiation zone 110, a first cleaning zone 120, a first drying zone 130, a nitration zone 140, a second cleaning zone 150, and a second drying zone 160 which are arranged in sequence. A guide roller 171 is provided in each zone to allow the material to be transmitted through each zone in sequence, which is easy to control and operate, and can improve work efficiency.
[0079] A first open reactor 111 for containing a reaction solution for dissolving lithium is provided in the lithiation zone 110. The guide roller 171 is located in the first open reactor 111. A solution that can dissolve lithium is placed in the first open reactor 111 to cause the outer first metal lithium layer 101 and the second metal lithium layer 105 to fall off, thereby obtaining a composite copper foil.
[0080] like Figure 4 and Figure 5 The device of the lithiation zone is shown in FIG. A first gas extraction device 002 is set at the top of the lithiation zone. The first gas extraction device includes a pump pressure tank to realize the gas extraction function and collect the hydrogen generated by the reaction. A wet filter cloth is used at the tail end of the first gas extraction device 002 to filter and absorb organic acids, alcohols and water entrained in the hydrogen. According to the characteristic of low density of hydrogen, the water drainage method can be used to collect hydrogen.
[0081] Preferably, a collection tank with a sloped bottom is used for reaction in the lithiation zone, such as a Y-shaped tank, and the droplets are collected along the slope. However, the shape of the collection device is not limited to the Y-shape, and the slope is the main control factor. Other shapes with slopes can easily collect droplets.
[0082] In some embodiments, a unwinding shaft 001 is provided at one end of the lithiation zone, a winding shaft 003 is provided at the end of the device (the second drying zone 160), and a plurality of tension guide rollers 006 are provided in the reaction tank of the lithiation zone, so that the lithium composite copper foil composite tape or composite copper foil is transmitted sequentially through the unwinding shaft 001, a plurality of tension guide rollers 006 and the winding shaft 003.
[0083] The lithiation zone uses a solution of organic weak acid reacting with metallic lithium. The reaction is violent, and the amount of organic solution and the reaction time need to be controlled. The organic solution can be sprayed out in an extremely fine spray manner, and the reaction time can be automatically adjusted in combination with the feedback of the amount of hydrogen collected. For example, the amount of hydrogen produced can be calculated based on the amount of lithium before the reaction, and then the reaction time can be adjusted based on the amount of hydrogen collected. When the amount of hydrogen collected reaches the theoretical amount, the reaction ends. During the reaction process, multiple tension guide rollers 006 can be used to increase the reaction area. The hydrogen produced by the reaction is collected by the drainage method and applied to the dilute nitric acid solution in the copper reaction zone for heating, thereby increasing the reaction efficiency of the copperization zone.
[0084] In some embodiments, in the lithiation zone, a first spray device 004 for spraying downward is provided above the plurality of tension guide rollers 006, and a second spray device 005 for spraying upward is provided below the tension guide rollers 006. The organic solution is sprayed out by the first spray device 004 and the second spray device 005, and the organic solution is made to submerge the plurality of tension guide rollers. The first spray device 004 and the second spray device 005 each include a plurality of nozzles, and the spray flow rate of each nozzle is greater than 4.2×10 -3mL / min, the diameter of the sprayed droplets is 3μm-15μm, and it can be calculated that each nozzle can spray at least 5 billion droplets per second. By adjusting the flow rate and droplet size, the purpose is to slow down the reaction rate and prevent violent reactions from causing safety accidents.
[0085] Specifically, there are differences in the composition of the spray in the high-pressure spray, in which the lithium spray is graded with different molar additions of organic acid, gradually increasing the organic acid content, and taking the maximum solubility of the organic acid in the corresponding water and ethanol mixture as the maximum molar concentration of the nozzle. The number and flow of nozzles can be adjusted according to parameters such as the thickness of the waste belt to be treated and the area to be treated, and the intensity of the reaction can be controlled to achieve the recovery of metal lithium into organic acid lithium.
[0086] In some embodiments, the initial running speed is controlled to be 0.05 m / min-0.3 m / min (such as 0.05 m / min, 0.1 m / min, 0.2 m / min, 0.3 m / min, etc.). The spray devices above and below the multiple tension guide rollers 006 are filled with a weak organic acid mixture or an organic substance with a hydroxyl group, and the reaction formula is as follows:
[0087] 2R-COOH+2Li=2R-COOLi+H2↑;
[0088] 2R-OH+2Li=2R-OLi+H2↑;
[0089] The embodiment of the present invention can achieve 100% recovery of metallic lithium to obtain a high-value organic acid lithium solution.
[0090] The degree of lithium metal digestion is determined based on the amount of hydrogen collected, thereby controlling the unwinding speed. The unwinding rate is calculated as follows:
[0091] y = -0.067x + 2;
[0092] In the formula, y represents the running speed, in m / min; x represents the hydrogen production volume, in L. The calculation process ignores the units and only performs numerical calculations. The calculation formula for the unwinding rate is not limited to the above formula.
[0093] S2. Cleaning and drying
[0094] like Figure 3 and Figure 4 As shown, the lithium composite copper foil composite tape passes through the lithiation zone through the guide roller and then passes through the first cleaning zone 120 (i.e. Figure 3 The copper foil is then cleaned in the middle cleaning zone and in the first drying zone 130, and then dried in the drying zone to obtain a composite copper foil.
[0095] In some embodiments, the solvent used in the cleaning process is selected from at least one of ethanol, methanol and water (for example, pure water), and the solvent used in the cleaning process can be any one or more of the above. In a preferred embodiment, the solvent used in the cleaning process is ethanol with a mass fraction of 50%-75%. The ethanol aqueous solution in this concentration range is easy to obtain and inexpensive, and can clean the organic acid and a small amount of unreacted lithium on the surface, making the surface clean and bright.
[0096] In some embodiments, the drying oven can be carried out in a blast drying oven, which can continuously process the materials from the cleaning area. The drying temperature is controlled to be 30°C-80°C, and solvents such as ethanol can be better removed within this temperature range.
[0097] like Figure 4 As shown, the first cleaning zone 120 is provided with a first cleaning container 121 for containing a cleaning solvent, and the guide roller 171 is located in the first cleaning container 121. In the first cleaning zone 120, the composite copper foil is cleaned with a solvent to remove the unreacted reagent remaining on the surface.
[0098] The first drying zone 130 is provided with a first drying box 131 . The guide roller 171 is located in the first drying box 131 . The first drying box 131 removes the solvent on the surface of the composite copper foil by heating.
[0099] S3, Dissolved Copper
[0100] like Figure 3 and Figure 4 As shown, the composite copper foil output from the drying area enters the nitrification area 140 and reacts with the nitric acid mixture to dissolve the first copper layer and the second copper layer on the surface while recovering the diaphragm layer.
[0101] In some embodiments, the nitric oxide obtained by the reaction in the nitric acid mixture can be collected and reacted with an oxygen-containing atmosphere and water in an oxidation zone to obtain a nitric acid solution, and the nitric acid solution obtained by the reaction can be recycled to prepare the nitric acid mixture.
[0102] In some embodiments, the nitric acid mixture may be dilute nitric acid with a mass fraction of 20%-50%, and the concentration of the dilute nitric acid may be 20%, 30%, 40%, 50%, etc. The chemical reaction equation is as follows:
[0103] 3Cu+8HNO3(dilute)=3Cu(NO3)2+2NO↑+4H2O;
[0104] like Figure 4 and Figure 6As shown, a second open reactor 141 for holding a reaction solution containing nitric acid is provided in the nitrification zone 140, and a guide roller 171 is located in the second open reactor 141. The second copper layer 104 and the first copper layer 102 in the composite copper foil in the nitrification zone 140 are dissolved, and the middle diaphragm layer 103 is recovered and enters the subsequent second cleaning zone 150 and the second drying zone 160. Multiple tension guide rollers 006 are provided in the reaction container of the nitrification zone 140. The number of tension guide rollers 006 in the nitrification zone is not limited. During operation, the guide rollers are submerged by the dilute nitric acid solution, which can increase the reaction area and improve the reaction rate.
[0105] Furthermore, since nitric oxide is toxic, a second exhaust device 007 is provided at the top of the nitrification zone to collect the nitric oxide produced by the reaction through the second exhaust device 007. The nitric oxide collected in the nitrification zone is reacted with water under an oxygen-containing atmosphere to obtain a nitric acid solution, which is circulated to the nitrification zone. The chemical reaction equation is as follows:
[0106] 4NO+3O2+2H2O=4HNO3.
[0107] In some embodiments, a heating device 008 is further provided on the nitration zone 140. The heating device 008 uses the hydrogen collected in the lithiation zone to burn and provide heat to accelerate the nitration reaction rate. The heating device can be located below the reaction pool in the nitration zone, but is not limited thereto.
[0108] Furthermore, the membrane layer (PP / PET film) output from the nitrification zone can be passed through the second cleaning zone 150 (i.e. Figure 3 The product is cleaned in the cleaning zone after the intermediate nitrification zone to remove unreacted ions on the surface, and then passes through the second drying zone 160 and enters the winding zone to wind up the finished product.
[0109] The structure of the second cleaning zone 150 is similar to that of the first cleaning zone 120. The second cleaning zone 150 is provided with a second cleaning container 151 for containing a cleaning solvent, and a guide roller 171 is provided in the second cleaning container 151. The structure of the second drying zone 160 is similar to that of the first drying zone 130. The second drying zone 160 is provided with a second drying box 161, and a guide roller 171 is provided in the second drying box 161. The strip is conveyed by the guide roller 171, so that the strip passes through the lithiation zone 110, the first cleaning zone 120, the first drying zone 130, the nitration zone 140, the second cleaning zone 150, and the second drying zone 160 in sequence.
[0110] It should be noted that the embodiment of the present invention can realize roll-to-roll processing of waste lithium composite copper foil composite strip, which improves the efficiency by at least 80% compared with the current process, and can recycle 100% of metallic lithium and PP film, and the recovery rate of copper can reach more than 95%. In particular, the recycled roll PP film can be used as a strip support film to realize waste utilization and protect the environment and resources.
[0111] In addition, the method provided in the embodiment of the present invention can be applied to the recovery of pure lithium strips, ultra-thin lithium strips, ultra-thin lithium-copper composite strips, lithium alloy strips and other strips, and can also be applied to the recovery of copper metal in materials such as composite copper foils below 10 μm, electrolytic copper foils, and microporous copper foils. It has a high degree of industrialization and can improve the recovery efficiency. The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0112] It should be noted that the following embodiments all provide a method for recycling lithium composite copper foil composite strips, such as Figure 3-Figure 6 As shown, the waste lithium composite copper foil composite tape is subjected to lithium and organic acid reaction in the lithiation zone, and then continuously cleaned and dried, and then placed in the nitration zone to complete the copper nitration reaction, and finally a roll of PP / PET film is obtained for recovery.
[0113] The organic acid used in the lithiation zone of Examples 1-3 is oxalic acid.
[0114] Example 1 - Recycling of lithium composite copper foil composite strip
[0115] (1) Provide a waste lithium copper composite tape to be processed. The copper foil (i.e., the first copper layer 102 and the second copper layer 104) of the lithium composite copper foil composite tape are both pure metal copper (prepared by magnetron sputtering process), the copper layer thickness is 1.5 μm, and the width is 200 mm; the waste lithium (i.e., the first metal lithium layer 101 and the second metal lithium layer 105) is 20 μm thick and 180 mm wide; the diaphragm layer 103 is a PP film with a thickness of 3 μm and a width of 200 μm. The composite tape is 50 m long, and the estimated amount of metal lithium to be processed is 192.24 g. The lithium composite copper foil composite tape is threaded, and the threading tension is 10 N.
[0116] (2) Open the program, the guide roller starts to rotate, the initial rotation speed is set to 0.08m / min, the waste composite belt to be processed enters the lithiation zone, and the 19 nozzle devices in the lithiation zone are opened. The single spray flow rate is shown in the table below. The high-pressure micro-mist spray nozzle can produce 5 billion droplets per second, and the diameter of the droplets is 3-15μm. The contents of each nozzle device are as follows, a total of 19 nozzle devices and 76 nozzles.
[0117] Table 1: Nozzle organic acid parameter diagram
[0118]
[0119]
[0120] The waste composite belt undergoes a lithiation reaction. The metal lithium follows the reaction steps of oxalic acid, water, and ethanol. 1 mol of hydrogen requires 2 mol of metal lithium to react. The running speed is 0.08m / min. The reaction product is a mixture of lithium oxalate and lithium hydroxide. A Y-type collector is used in the lithiation zone to purify and separate the lithium oxalate. The spray flow rate and lithium consumption are as follows:
[0121] Table 2: Spray flow rate and lithium consumption
[0122]
[0123] This time, 19 nozzle devices were selected, with a total nozzle flow rate of 76.73 ml / min, and the amount of metallic lithium consumed was 0.3278 g / min. Theoretically, it takes 586 minutes for the metallic lithium to completely react to generate organic acid lithium for recovery.
[0124] After the lithiation reaction is completed, a composite copper foil strip is obtained, and a small amount of metallic lithium, oxalic acid, lithium oxalate and other compounds may exist on the surface.
[0125] The composite copper foil strip enters the cleaning area. The cleaning solution is an ethanol solution, the main component of which is ethanol, with a mass fraction of 60%. It can dissolve 99% of the above mixture and is easy to dry. At this stage, the surface of the strip can be observed with the naked eye to be orange-red or a similar color.
[0126] The cleaned composite copper foil enters the blast drying oven and then the nitrification zone. The main reaction equation is as follows: 3Cu+8HNO3(dilute)=3Cu(NO3)2+2NO↑+4H2O;
[0127] The nitration reaction pool contains several tension guide rollers, which are submerged in dilute nitric acid solution and made of alkali corrosion resistant material. The main component of the nitration reaction pool is dilute nitric acid with a mass fraction of 35%. The other component is pure water.
[0128] Since nitric oxide is toxic, a powerful exhaust device is arranged above the nitrification area, and a solution containing air and water is sent into it through a pipe to generate dilute nitric acid, which is then circulated and used in the nitrification tank.
[0129] The strip from the nitrification zone is cleaned and dried to obtain a PP / PET film.
[0130] After testing, there is no metallic lithium on the processed PP film roll, and the surface is clean, transparent, and the transmittance reaches 100%, and there is basically no metallic copper residue. The theoretical recovery time for the complete reaction of metallic lithium to generate organic acid lithium is at most 586 minutes, and the amount of lithium oxalate recovered from the waste of lithium composite copper foil composite tape is at most 27.7 mol, and the concentration is at most 0.62 mol / L. After testing, it can be obtained that the PP film thickness is 3μm, the width is 200mm, and the length is 50m.
[0131] Example 2 - Recycling Ultra-thin Lithium Composite Copper Foil Copper Composite Strip
[0132] (1) Provide a waste lithium copper composite tape to be processed. The copper foil of the lithium composite copper foil composite tape is a composite copper foil with a thickness of 6 μm, wherein the copper layer is 1.5 μm and a width of 200 mm; the waste lithium is 20 μm thick and 180 mm wide, and is double-sided lithium; the separator layer 103 is a PP film with a thickness of 3 μm and a width of 200 μm. The length of the composite tape is 50 m, and the estimated amount of metal lithium to be processed is 192.24 g. The lithium composite copper foil composite tape is threaded, and the threading tension is 15 N.
[0133] (2) Open the program, the guide roller starts to rotate, the initial rotation speed is set to 0.3 / min, the waste composite belt to be processed enters the lithiation zone, and the 31 nozzle devices in the lithiation zone are opened. The single spray flow rate is shown in the table below. The high-pressure micro-mist spray nozzle can produce 5 billion droplets per second, and the diameter of the droplets is 3 to 15 μm. The content of each nozzle device is as follows, a total of 31 nozzle devices, 124 nozzles.
[0134] Table 3: Nozzle organic acid parameter diagram
[0135]
[0136]
[0137] The waste composite belt undergoes a lithiation reaction. The metal lithium follows the reaction steps of oxalic acid, water, and ethanol. 1 mol of hydrogen requires 2 mol of metal lithium to react. The running speed is 0.3m / min. The reaction product is a mixture of lithium oxalate and lithium hydroxide. A Y-type collector is used in the lithiation zone to purify and separate the lithium oxalate. The spray flow rate and lithium consumption are as follows:
[0138] Table 4: Spray flow rate and lithium consumption
[0139]
[0140]
[0141] This time, 31 nozzle devices were selected, with a total of 124 nozzles. The total nozzle flow rate was 168.3 ml / min, and the amount of metallic lithium consumed was 1.165 g / min. Theoretically, it takes 165 minutes for the metallic lithium to completely react to generate organic acid lithium for recovery.
[0142] After the lithiation reaction is completed, the composite copper foil strip is obtained, and there may be a small amount of metallic lithium, oxalic acid, lithium oxalate and other compounds on the surface. The composite copper foil strip enters the cleaning area. The cleaning solution is an ethanol solution, the main component of which is ethanol, with a mass fraction of 70%, which can dissolve 99% of the above mixture and is convenient for drying. At this stage, the surface of the strip can be observed with the naked eye to be orange-red or similar colors.
[0143] The cleaned composite copper foil enters the blast drying oven and then the nitrification zone. The nitrification reaction pool contains several tension guide rollers, which are submerged in dilute nitric acid solution and made of alkali corrosion resistant materials. The main component of the nitrification reaction pool is dilute nitric acid, with a mass fraction of 30%, and the other components are distilled water.
[0144] Since nitric oxide is toxic, a powerful exhaust device is arranged above the nitrification area, and a solution containing air and water is sent into it through a pipe to generate dilute nitric acid, which can be recycled and used in the nitrification tank.
[0145] The strip from the nitrification zone is cleaned and dried to obtain a PP / PET film.
[0146] After testing, there is no metallic lithium on the processed PP / PET film rolls, and the surface is clean, transparent, and the light transmittance reaches 100%. There is basically no metallic copper residue. Theoretically, the recovery time of metallic lithium completely reacting to generate organic acid lithium is at most 165 minutes, and the amount of lithium oxalate recovered from the waste of lithium composite copper foil composite tape is at most 27.7 mol, and the concentration is at most 1 mol / L. After testing, the PP film thickness is 3μm, the width is 200mm, and the length is 50m.
[0147] Example 3 - Recycling of ultra-thin lithium strips and PP / PET films
[0148] When the thickness of ultra-thin lithium ribbon is less than 20μm, the tension will cause the ribbon to break during roll-to-roll production, thus making it impossible to achieve self-support. PET or PP film is required to provide a stress point for it. This process mainly involves the lithiation zone, which collects metallic lithium and PET or PP film, and the nitration zone is not used.
[0149] (1) Provide a waste lithium ribbon to be processed, the lithium ribbon is 5 μm, the width is 160 mm, the supporting film PET film is 200 mm wide, the thickness is 50 μm, and the length of both is 50 m. 21.36 g of lithium is to be recovered. The ultra-thin waste lithium ribbon using the PET film as the supporting film is threaded, and the threading tension is 15 N.
[0150] (2) The waste ultra-thin lithium strip is placed in the guide roller and enters the lithiation zone. The oxalic acid solution reacts with the metallic lithium to generate lithium oxalate and hydrogen. The program is opened, the guide roller starts to rotate, and the initial rotation speed is set to 0.3 / min. The waste composite strip to be processed enters the lithiation zone. The 31 spray nozzle devices in the lithiation zone are opened. The single spray flow rate is shown in the table below. The spray high-pressure micro-mist spray nozzle can produce 5 billion droplets per second, and the diameter of the droplets is 3 to 15 μm. The contents of each nozzle device are as follows, a total of 31 nozzle devices and 124 nozzles.
[0151] Table 5: Sprinkler device content
[0152]
[0153]
[0154] The waste composite belt undergoes a lithiation reaction. The metal lithium follows the reaction steps of oxalic acid, water, and ethanol. 1 mol of hydrogen requires 2 mol of metal lithium to react. The running speed is 0.3m / min. The reaction product is a mixture of lithium oxalate and lithium hydroxide. A Y-type collector is used in the lithiation zone to purify and separate the lithium oxalate. The spray flow rate and lithium consumption are as follows:
[0155] Table 6: Spray flow rate and lithium consumption
[0156]
[0157]
[0158] This time, 31 nozzle devices were selected, with a total of 124 nozzles. The total nozzle flow rate was 168.3 ml / min, and the amount of metallic lithium consumed was 1.165 g / min. Theoretically, it takes 18.3 minutes for the metallic lithium to completely react to generate organic acid lithium for recovery.
[0159] After the lithiation reaction is completed, the PET strip is obtained, and a small amount of metallic lithium, oxalic acid, lithium oxalate and other compounds may exist on the surface. After cleaning, it is dried and rolled up.
[0160] The nitrification zone was not used in this embodiment.
[0161] After testing, there is no bright white metallic lithium, black lithium compound, or white lithium carbonate on the processed PET film rolls, and the surface is clean, transparent, and has a light transmittance of 100%. The theoretical recovery time for the waste ultra-thin 5μm lithium strip to completely generate lithium oxalate is at most 18.3min, and the amount of lithium oxalate recovered from the waste material is at most 3.1mol, with a concentration of at most 1mol / L. The width of the recycled support film PET film is 200mm, the thickness is 50 microns, and the length is 50m.
[0162] Example 4 - Acetic acid recovery of lithium composite copper foil composite strip
[0163] Acetic acid has a high solubility in water and ethanol, and the maximum concentration of organic acid in the nozzle can be increased according to the amount of lithium treated.
[0164] (1) Provide waste lithium copper composite tape to be processed. The copper foil of the lithium composite copper foil composite tape is composite copper foil with a thickness of 6 μm and a width of 200 mm; the waste lithium has a thickness of 20 μm and a width of 180 mm, and is double-sided lithium; the separator layer 103 is a PP film with a thickness of 3 μm and a width of 200 μm. The length of the composite tape is 50 m, and the estimated amount of metal lithium to be processed is 192.24 g. The lithium composite copper foil composite tape is threaded with a threading tension of 10 N.
[0165] (2) Open the program, the guide roller starts to rotate, the initial rotation speed is set to 0.3 / min, the waste composite belt to be processed enters the lithiation zone, and the 31 nozzle devices in the lithiation zone are opened. The single spray flow rate is shown in the table below. The high-pressure micro-mist spray nozzle can produce 5 billion droplets per second, and the diameter of the droplets is 3 to 15 μm. The content of each nozzle device is as follows, a total of 31 nozzle devices, 124 nozzles.
[0166] Table 7: Nozzle organic acid parameter diagram
[0167]
[0168]
[0169] This time, 31 nozzle devices were selected, with a total of 124 nozzles. The total nozzle flow rate was 168.3 ml / min, and the lithium consumption was 2.1 g / min. Theoretically, it takes 91.5 minutes for the metallic lithium to completely react to generate lithium acetate for recovery.
[0170] The waste composite belt undergoes lithiation reaction. The metallic lithium follows the reaction steps of acetic acid, water and ethanol. 2 mol of metallic lithium is required to generate 1 mol of hydrogen. The degree of reaction is determined by observing the amount of hydrogen collected. The initial operating speed is 2m / min.
[0171] The reaction product is a mixture of lithium acetate and lithium hydroxide. A Y-type collector is used in the lithiation zone to purify and separate lithium acetate. After the lithiation reaction is completed, a composite copper foil strip is obtained, and a small amount of metallic lithium, acetic acid, lithium acetate and other compounds may exist on the surface.
[0172] After the lithiation reaction is completed, the composite copper foil strip is obtained, and a small amount of metallic lithium, oxalic acid, lithium oxalate and other compounds may exist on the surface. After cleaning, it is dried and rolled up.
[0173] The composite copper foil strip enters the cleaning area. The solution in the cleaning area is an ethanol solution, the main component of which is ethanol with a mass fraction of 60%. It can dissolve 99% of the above mixture and is convenient for drying.
[0174] The cleaned composite copper foil enters the blast drying oven and then the nitrification zone. The nitrification reaction pool contains several tension guide rollers, which are submerged in dilute nitric acid solution and made of alkali corrosion resistant materials. The main component of the nitrification reaction pool is dilute nitric acid, with a mass fraction of 25%, and the other components are pure water.
[0175] Since nitric oxide is toxic, a powerful exhaust device is arranged above the nitrification area, and a solution containing air and water is sent into it through a pipe to generate dilute nitric acid, which can be recycled and used in the nitrification tank.
[0176] The strip from the nitrification zone is cleaned and dried to obtain a PP film.
[0177] After testing, there is no bright white metallic lithium, black lithium compound, or white lithium carbonate on the processed PET film roll, and the surface is clean, transparent, and has a light transmittance of 100%. The 20μm lithium strip was discarded, and the amount of metallic lithium processed was 192.24g. Theoretically, it takes 91.5min for the metallic lithium to completely react and generate lithium acetate for recycling. The amount of lithium acetate recovered from the waste material is at most 27.7mol, and the concentration is at most 1.8mol / L. The width of the recycled support film PP film is 200mm, the thickness is 6μm, and the length is 50m.
[0178] Example 5 and Example 6 are similar to Example 4, except that the organic acid in the lithiation zone is replaced by tartaric acid and citric acid, respectively.
[0179] Example 7 - Recycling of composite copper foil
[0180] The only difference from Example 1 is that the lithiation zone is not used, and the PP film / PET film in the waste composite copper foil is directly recovered.
[0181] Provide waste composite copper foil to be processed, with a thickness of 6μm and a width of 200mm. The composite copper foil enters the nitrification zone after entering the blast drying oven. Among them, the nitrification reaction pool contains several tension guide rollers, and the guide rollers are submerged in dilute nitric acid solution. The guide rollers are made of alkali corrosion resistant materials. The main component of the nitrification reaction pool is dilute nitric acid, with a mass fraction of 25%, and the other components are deionized water.
[0182] Since nitric oxide is toxic, a powerful exhaust device is arranged above the nitrification area, and a solution containing air and water is sent into it through a pipe to generate dilute nitric acid, which can be recycled and used in the nitrification tank.
[0183] The strip from the nitrification zone is cleaned and dried to obtain a PP / PET film.
[0184] After testing, it was found that there were no impurities on the processed rolled PET film, and the surface was clean and transparent. The recycled support film PP film had a width of 200 mm, a thickness of 6 μm, and a length of 50 m.
[0185] Comparative Example 1
[0186] (1) Provide waste lithium copper composite tape to be processed. The copper foil of the lithium composite copper foil composite tape is composite copper foil with a thickness of 6 μm and a width of 200 mm; the waste lithium has a thickness of 20 μm and a width of 180 mm, and is double-sided lithium; the separator layer 103 is a PP film with a thickness of 3 μm and a width of 200 μm. The length of the composite tape is 50 m, and the estimated amount of metal lithium to be processed is 192.24 g. The lithium composite copper foil composite tape is threaded with a threading tension of 10 N.
[0187] (2) Open the program, the guide roller starts to rotate, the initial rotation speed is set to 0.3 / min, the waste composite belt to be processed enters the lithiation zone, and the 31 spray nozzles in the lithiation zone are turned on. The high-pressure micro-mist spray nozzle can produce 5 billion droplets per second, and the diameter of the droplets is 3 to 15 μm. The contents of each nozzle device are as follows, a total of 31 nozzle devices and 124 nozzles. The nozzle liquid is 1.6 mol oxalic acid dissolved in 5L water and 5L ethanol solution, the concentration is 1.6 mol / L, the spray reacts violently with metallic lithium, and the risk factor is high. A large amount of heat is released, causing the PP film to deform at high temperature and can no longer be recycled.
[0188] In comparative example 1, the organic acid content in each nozzle is consistent and large, resulting in a high risk factor. In the embodiment of the present invention, the organic acid content in the nozzle is gradually increased by regulating the reaction rate, slowing down the heat release, and reducing the risk.
[0189] Comparative Example 2
[0190] (1) Provide waste lithium copper composite tape to be processed. The copper foil of the lithium composite copper foil composite tape is a composite copper foil with a thickness of 6 μm and a width of 200 mm. The waste lithium has a thickness of 20 μm and a width of 180 mm, and is double-sided lithium. The separator layer 103 is a PP film with a thickness of 3 μm and a width of 200 μm. The length of the composite tape is 50 m, and the estimated amount of metal lithium to be processed is 192.24 g. The lithium composite copper foil composite tape is threaded, and the threading tension is 10 N.
[0191] (2) Open the program, the guide roller starts to rotate, the initial rotation speed is set to 0.3 / min, the waste composite belt to be processed enters the lithiation zone, and the 31 spray nozzle devices in the lithiation zone are opened. The single spray flow rate is shown in Table 8. The spray high-pressure micro-mist spray nozzle can produce 5 billion droplets per second, and the diameter of the droplets is 3-15μm. The content of each nozzle device is as follows, a total of 31 nozzle devices, 124 nozzles. The nozzle liquid is a mixed solution of 5L water and 5L ethanol, and the organic acid concentration is 0mol / L. Water reacts with waste metal lithium to obtain a product of lithium hydroxide at most 27.7mol, organic acid lithium 0mol, and the task of recovering high-value organic acid lithium is not completed, but PP / PET film recovery can be completed.
[0192] Table 8: Nozzle organic acid parameter diagram
[0193]
[0194]
[0195] It can be seen from Comparative Example 2 that the recovery of high-value organic acid lithium cannot be achieved without adding organic acid treatment.
[0196] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for recycling lithium composite copper foil composite strip, characterized in that: The lithium composite copper foil composite tape comprises a first metal lithium layer, a first copper layer, a diaphragm layer, a second copper layer and a second metal lithium layer which are arranged in sequence, and the method comprises: The lithium composite copper foil and composite tape are reacted in an organic solution containing carboxyl or hydroxyl groups to dissolve the first metal lithium layer and the second metal lithium layer to obtain a composite copper foil; The composite copper foil is reacted in a nitric acid mixture to dissolve the first copper layer and the second copper layer on the surface and recover the diaphragm layer at the same time.
2. The method according to claim 1, characterized in that The organic solution is a mixed solution of an organic acid, an organic alcohol solvent and water, and the organic lithium salt obtained by the reaction is recovered as a pharmaceutical raw material; Preferably, the organic acid is selected from at least one of oxalic acid, acetic acid, tartaric acid and citric acid; Preferably, the organic alcohol solvent is ethanol, and the volume ratio of the organic alcohol solvent to water is 1:(0.5-1.5).
3. The method according to claim 1, characterized in that collecting the nitric oxide obtained by the reaction in the nitric acid mixture, reacting it with water in an oxygen-containing atmosphere to obtain a nitric acid solution, and using the nitric acid solution to prepare the nitric acid mixture; Preferably, the nitric acid mixture is dilute nitric acid with a mass fraction of 20%-50%.
4. The method according to any one of claims 1 to 3, characterized in that After the lithium composite copper foil composite tape is reacted in the organic solution, it is washed and dried, and then placed in the nitric acid mixture to react; Preferably, the solvent used in the cleaning process is selected from at least one of ethanol, methanol and water; more preferably, the solvent used in the cleaning process is ethanol with a mass fraction of 50%-75%; Preferably, the drying temperature is controlled at 30°C-80°C.
5. The method according to claim 4, characterized in that The lithium composite copper foil composite tape is sequentially processed through a lithiation zone, a first cleaning zone, a drying zone and a nitration zone by a guide roller; in the lithiation zone, the lithium composite copper foil composite tape is reacted in the organic solution; in the first cleaning zone, the lithium composite copper foil composite tape is cleaned with a solvent; and then the composite copper foil is dried in the drying zone to obtain a composite copper foil; and in the nitration zone, the composite copper foil reacts with the nitric acid mixture.
6. The method according to claim 5, characterized in that collecting hydrogen generated during the reaction with the organic solution and using it to provide heat for the nitrification zone after combustion; Preferably, a first gas extraction device is provided in the lithiation zone, and organic acids, alcohols and water are filtered by a wet filter cloth in the first gas extraction device, and hydrogen is collected by a drainage method; Preferably, the reaction is carried out in the lithiation zone using a collecting tank with a sloped bottom.
7. The method according to claim 6, characterized in that A reel is provided at one end of the lithiation zone, a reel is provided at the end of the device, and a plurality of tension guide rollers are provided in the reaction vessels of the lithiation zone and the nitration zone, so that the lithium composite copper foil composite tape or the composite copper foil is sequentially transmitted through the reel, the plurality of tension guide rollers and the reel; Preferably, the first gas extraction device is arranged at the top of the lithiation zone.
8. The method according to claim 7, characterized in that In the lithiation zone, a first spray device for spraying downward is arranged above the plurality of tension guide rollers, and a second spray device for spraying upward is arranged below the tension guide rollers, and the organic solution is sprayed out by using the first spray device and the second spray device; Preferably, the first spray device and the second spray device each include a plurality of spray heads, and the spray flow rate of each spray head is greater than 4.2×10 -3 mL / min, the diameter of the sprayed droplets is 3μm-15μm; Preferably, the initial running speed is controlled to be 0.05 m / min-0.3 m / min, and then the unwinding speed is controlled according to the amount of collected hydrogen.
9. The method according to claim 5, characterized in that A second exhaust device is provided at the top of the nitrification zone to collect the nitric oxide produced by the reaction through the second exhaust device; the nitric oxide collected in the nitrification zone reacts with water under an oxygen-containing atmosphere to obtain a nitric acid solution, and the nitric acid solution is circulated to the nitrification zone; A heating device is also provided on the nitration zone, and the heating device uses the hydrogen collected in the lithiation zone to burn and provide heat; Preferably, after passing through the nitrification zone, the strip continues to pass through a second cleaning zone for cleaning and then is wound up.
10. The method according to claim 1, characterized in that The thickness of the diaphragm layer is 1 μm-10 μm, the thickness of the first metal lithium layer and the second metal lithium layer are both 5 μm-100 μm, and the thickness of the first copper layer and the second copper layer are both 1 μm-3 μm; Preferably, the diaphragm layer is selected from at least one of a PP film and a PET film.